2015
DOI: 10.1136/flgastro-2014-100537
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in the UK management of upper GI bleeding: is there evidence of reduced UK training experience?

Abstract: Objective The aim of this study was to evaluate UK trainee experience in endoscopy for acute upper gastrointestinal bleeding (AUGIB). Methods Data was prospectively collected from all patients presenting to South Yorkshire Hospitals with AUGIB from September 2011 to December 2011 and compared with data from 1996. Concurrently, all gastroenterology trainees registered with the British Society of Gastroenterology were invited to respond to a web-based questionnaire regarding their experience in AUGIB management.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…19 Sustainability of services for UGIB also requires that those appointed to consultant posts have had adequate training and experience. 20 ■…”
Section: Organisation Of Ugib Servicesmentioning
confidence: 99%
“…19 Sustainability of services for UGIB also requires that those appointed to consultant posts have had adequate training and experience. 20 ■…”
Section: Organisation Of Ugib Servicesmentioning
confidence: 99%
“…Training in AUGIB within the UK has been a persistently contentious issue 11. Previous data point to a reduction in trainee exposure to AUGIB cases over time,6 particularly with high-risk cases, and lack of confidence in final-year trainees with managing the condition 5. At present, there is no UK AUGIB curriculum or minimum procedural numbers recommended by JAG or the British Society of Gastroenterology (BSG) to benchmark competence in AUGIB haemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…From 2021, higher specialist training will be shortened from 5 to 4 years under ‘Shape of Training’ proposals 4. This has raised concerns regarding competency acquisition in endoscopy, particularly when shortfalls have been reported during the existing 5-year training period 5–7…”
Section: Introductionmentioning
confidence: 99%
“…The recent NCEPOD identified that 53% of consultants contributing to an on-call UGIB rota did not feel confident in their ability to glue gastric varices 8. Gastroenterology trainees in the UK report a deficiency in their training and exposure to the management of UGIB especially in the out-of-hours period and with more difficult cases, with 21% of trainees reporting that they were not satisfied with the training they received 26. There is a clear need to develop structured therapeutic endoscopy training for UGIB in the UK.…”
Section: Future Potentialmentioning
confidence: 99%